2020
DOI: 10.1111/ggi.13880
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescription patterns and factors associated with polypharmacy in >1 million older adults in Tokyo

Abstract: Aim To determine the patterns of concomitant drug use for chronic diseases and examine the risk factors of polypharmacy in older outpatients. Methods Data were extracted from an anonymized health insurance claims database of a public insurance program for older adults in Tokyo, Japan. We analyzed individuals aged ≥75 years who had visited an outpatient clinic, and were regularly prescribed orally administered drugs for chronic diseases for ≥14 days between May and August 2014. The prescription patterns for 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
4
17
1
1
Order By: Relevance
“…This study investigated the association between polypharmacy and poor oral health status in patients admitted to the recovery and rehabilitation ward. Polypharmacy was detected in 56.9% of hospitalized patients aged ≥65, echoing the findings of previous studies in Japan 21 . Three OHAT subscales were associated with polypharmacy: “Saliva,” “Natural teeth” and “Oral cleanliness.” The association between polypharmacy and poor oral health status was observed even after adjusting for the potential confounding variables, namely age, sex, BMI, comorbidities, FIM‐C, FIM‐M and PIMs‐DM.…”
Section: Discussionsupporting
confidence: 82%
“…This study investigated the association between polypharmacy and poor oral health status in patients admitted to the recovery and rehabilitation ward. Polypharmacy was detected in 56.9% of hospitalized patients aged ≥65, echoing the findings of previous studies in Japan 21 . Three OHAT subscales were associated with polypharmacy: “Saliva,” “Natural teeth” and “Oral cleanliness.” The association between polypharmacy and poor oral health status was observed even after adjusting for the potential confounding variables, namely age, sex, BMI, comorbidities, FIM‐C, FIM‐M and PIMs‐DM.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of antidepressants was twice as high as that in older outpatients aged ≥75 years (3.7%) in Japan. 45 However, the prescription rate in our study was considerably lower compared with that reported in studies conducted in other countries, with approximately one-fifth to two-thirds of NH residents with or without dementia reported to have received antidepressants. 11-17 20 We also found that older age was associated with infrequent use of antidepressants, which is consistent with findings from previous studies; however, we did not observe a significantly greater use of antidepressants in women, which has been reported in previous studies.…”
Section: Discussioncontrasting
confidence: 87%
“…In a nationwide retrospective study using 240 million pharmacy claims data items, Onoue et al (2018) reported that 69.0% of elderly patients were PP(+) [ 9 ]. Ishizaki et al (2020) also reported that non-excessive PP (5–9 medications) and excessive PP (≥10 medications) was seen, respectively, in 45.3% and 18.2% elderly patients (≥75 years old) [ 7 ]. In our study (as shown in Table 2 ), old (≥75 years) patients had a significantly higher number of PP(+) patients as compared to pre-old (65–74 years) patients (76.5% vs. 52.7%, p = 0.003), and 64.1% PP(+) patients had a higher median age (75 years) compared to PP(–) patients (72 years), which is supported by previous studies [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pharmacokinetics and drug responsiveness in elderly patients differ from those in younger adult patients because of aging-related physiological changes, and interactions among drugs administered to treat multiple comorbidities might cause adverse drug events (ADEs) [ 2 , 3 ]. Polypharmacy (PP), the use of five or more medications, is a major problem in terms of increasing risk of ADEs in elderly patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Onoue et al (2018), in a nationwide retrospective study using 240 million pharmacy claim data items, reported that 69.0% of elderly patients are PP(+) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%